Рід Luzula DC. (Juncaceae) у флорі України - Ольшанський, І.Г.; Федорончук, М.М. (Український ботанічний журнал, 2012)
Представлен конспект рода Luzula DC. во флоре Украины. Для всех видов приведены номенклатурная цитация, основные синонимы, типы и сведения о распространении. Предложен ключ для определения видов. A synopsis of the genus Luzula in the flora of Ukraine is presented. Nomenclature citations, synonyms, types and distribution data are provided for each species. An identification key to the species is proposed.